SPECTRAL CHARACTERISTICS OF SIGNALS WITH CONTINUOUS POLARIZATION SHIFT KEYING - P. V. Anikin; S. S. Zhavoronkov; D. N. Jamanov (Научный вестник МГТУ ГА)
Results of the analysis of the spectral characteristics of signals with polarization shift keying with continuous sequential change of the angle of orientation are given. The values of the generalized coefficient of modulation depth and width of the energy spectrum for the polarized signals with different polarization index manipulation are dealt with.